Basic researchEffects of clodronate combined with hydroxyapatite on multi-directional differentiation of mesenchymal stromal cells - Liu, Xian; Bao, Chongyun; Hu, Jing; Yin, Guozhu; Luo, En (Archives of Medical Science, 2010)
Introduction : Bisphosphonates (BPs) can be locally used to improve the osteogenesis around hydroxyapatite (HA) implants. However, there are almost no reports discussing the effects of BPs in the bonding state with HA on bone mesenchymal stromal cells (BMSCs). Clodronate is a BP widely used in clinical practice. This study was designed to evaluate the effects of clodronate combined with HA on BMSCs’ multi-directional differentiation. Material and methods : The HA and clodronate-HA complex were prepared. BMSCs were isolated from Sprague-Dawley rat bone marrow and then the cells were cultured with both HA and clodronate-HA. The method of transcriptional and translational assay (MTT) and multi-directional induction (including osteogenic, adipogenic, and myogenic differentiation) were used to evaluate the effect of clodronate-HA on BMSC differentiation. Results : Scanning electron microscopy indicated active proliferation of the cells on clodronate-HA and HA. MTT of BMSCs cultured on clodronate-HA and HA demonstrated no significant differences between the two groups. BMSCs differentiated into osteocytes, adipocytes, and myocytes after being cultured with both clodronate-HA and HA. This indicated that BMSCs still retained multi-directional capability. The alkaline phosphatase activity of osteogenic induced BMSCs of both groups had no significant difference. However, there was a significant difference in total protein found between them. Conclusions : The results suggest that clodronate in the bonding state with HA has no obvious inhibition of the proliferation and activity of BMSCs on the complex, and there was no evidence of a negative effect on multi-directional capability of the BMSCs.